2018
DOI: 10.1038/s41598-018-19801-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Dynamics Effects using Pulse-Shaping Laser Sintering of Printed Silver Inks

Abstract: In recent years, additive manufacturing has been evolving towards flexible substrates for the fabrication of printable electronic devices and circuits. Generally polymer-based, these emerging substrates suffer from their heat sensitivity and low glass-transition temperatures. As such they require new highly-localized sintering processes to treat the electronic inks without damaging the polymer-based substrate. Laser-based sintering techniques have shown great promises to achieve high-quality sintering locally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Yeo et al [89] sintered the R2R printed Ag NPs layer by laser to a conductivity up to 20% of bulk Ag on PET substrates. Bolduc et al [90] indicated that controlling the incident laser pulse’s energy distribution in the time-domain was paramount to optimizing sintering process in Ag NPs based ink. A multi-step microsecond-pulsed laser process and a time-domain pulse-shaping modulation sintering caused a uniform and high conductive printed Ag trace on polymer substrates.…”
Section: Strategies Of Achieving Highly Conductive Ag Nps Based Inmentioning
confidence: 99%
“…Yeo et al [89] sintered the R2R printed Ag NPs layer by laser to a conductivity up to 20% of bulk Ag on PET substrates. Bolduc et al [90] indicated that controlling the incident laser pulse’s energy distribution in the time-domain was paramount to optimizing sintering process in Ag NPs based ink. A multi-step microsecond-pulsed laser process and a time-domain pulse-shaping modulation sintering caused a uniform and high conductive printed Ag trace on polymer substrates.…”
Section: Strategies Of Achieving Highly Conductive Ag Nps Based Inmentioning
confidence: 99%
“…The laser sintering approach heavily relies on the optical properties of nanoparticles in the film; one has to choose the radiation source according to their absorption spectrum. This can be easily achieved for the most commonly used metal nanoparticles (Au 38 , Ag 39 , Cu 31 ), whose plasmon resonance peaks are located in the visible part of the spectrum 40 , however sintering of TCO particles becomes a challenging task due to their high transparency in that spectral region. Nevertheless, it has been shown that effective sintering of such nanoparticles is feasible using UV excimer lasers by specifically adding compounds to the ink with high absorption at the incident beam wavelength 41–43 .…”
Section: Introductionmentioning
confidence: 99%
“…The jetting frequency was set at 500 Hz. We used a commercially available conductive silver ink DGP 40TE-20C (ANP, Pleasanton, CA, USA) that contains silver nanoparticles (Ag NPs) of sizes around 50 nm with 30–35 wt.% in triethylene glycol monomethyl ether solvent [39]. The substrate used for printing was a heat-stabilized polyethylene terephthalate (PET) polyester film (Melinex ST505, New Berlin, WI, USA).…”
Section: Methodsmentioning
confidence: 99%